2005
DOI: 10.1529/biophysj.104.049700
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Aggregates, Prefibrillar Amyloidogenic Oligomers, and Protofibrils Using Fluorescence Spectroscopy

Abstract: Transthyretin (TTR) is a protein linked to a number of different amyloid diseases including senile systemic amyloidosis and familial amyloidotic polyneuropathy. The transient nature of oligomeric intermediates of misfolded TTR that later mature into fibrillar aggregates makes them hard to study, and methods to study these species are sparse. In this work we explore a novel pathway for generation of prefibrillar aggregates of TTR, which provides important insight into TTR misfolding. Prefibrillar amyloidogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
280
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 316 publications
(300 citation statements)
references
References 29 publications
20
280
0
Order By: Relevance
“…[61] Using a combination of fluorescence methods and structural techniques, it has been shown that amyloid aggregation at pH 5.8 is characterized by the rapid formation (~ 10 seconds) of amorphous aggregates with sizes ranging from 50 to 500 nm. [40] Importantly, as determined by circular dichroism (CD), these aggregates do not contain -helical or -structure and they are unable to seed fibril formation. [40] It has also been demonstrated that the aggregates evolve into smaller structures (30-80 nm) after 30 minutes which agrees well with the time window of the aggregation process observed in our FSQ and ThT experiments ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[61] Using a combination of fluorescence methods and structural techniques, it has been shown that amyloid aggregation at pH 5.8 is characterized by the rapid formation (~ 10 seconds) of amorphous aggregates with sizes ranging from 50 to 500 nm. [40] Importantly, as determined by circular dichroism (CD), these aggregates do not contain -helical or -structure and they are unable to seed fibril formation. [40] It has also been demonstrated that the aggregates evolve into smaller structures (30-80 nm) after 30 minutes which agrees well with the time window of the aggregation process observed in our FSQ and ThT experiments ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…[40] Importantly, as determined by circular dichroism (CD), these aggregates do not contain -helical or -structure and they are unable to seed fibril formation. [40] It has also been demonstrated that the aggregates evolve into smaller structures (30-80 nm) after 30 minutes which agrees well with the time window of the aggregation process observed in our FSQ and ThT experiments ( Figure 5). The time scale of the initial growth phase is within our mixing time, so it is likely that with the time resolution of our assay, we are monitoring the disappearance of the initially formed aggregates as they slowly evolve into other morphologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We present a previously unidentified model system for investigating inhibitory mechanisms against amyloidosis in vivo and in vitro and believe that this system will be useful for the development of novel therapies. amyloid fibril formation | apolipoprotein A-II | inhibitory peptide | mouse | senile amyloidosis A myloidosis refers to a group of protein structural disorders characterized by the extracellular deposits of insoluble amyloid fibrils resulting from abnormal conformational changes (1)(2)(3)(4)(5). Amyloid fibrils have a characteristic ultrastructural appearance and a β-pleated sheet core structure that consists of full-length proteins and/or fragments of either WT or mutant proteins found in familial diseases (2,(6)(7)(8).…”
mentioning
confidence: 99%